Surveillance and Reduction Control of Escherichia coli and Diarrheagenic E. coli During the Pig Slaughtering Process in China - Wang, Lin; Liu, Na; Gao, Yubin; Liu, Junhui; Huang, Xiumei; Zhang, Qingqing; Li, Yuehua; Zhao, Jianmei; Wang, Junwei; Zhao, Ge (Frontiers in Veterinary Science, 2021)
The microbial contamination of pork during the slaughter process, especially that of the hygiene indicator bacteria, Escherichia coli, is closely related to the safety and quality of the meat. Some diarrheagenic E. coli can cause serious foodborne diseases, and pose a significant threat to human life and health. In order to ascertain the current status of E. coli and diarrheagenic E. coli contamination during the pig slaughter process in China, we conducted thorough monitoring of large-sized slaughterhouses, as well as small- or medium-sized slaughterhouses, in different provinces of China from 2019 to 2020. The overall positive rate of E. coli on the pork surface after slaughter was very high (97.07%). Both the amount of E. coli contamination and the positive ratio of diarrheagenic E. coli in large-sized slaughterhouses (7.50–13.33 CFU/cm2,3.44%) were lower than those in small- or medium-sized slaughterhouses (74.99–133.35 CFU/cm2,5.71%). Combined with the current status of sanitary control in slaughterhouses, we determined that pre-cooling treatment significantly reduced E. coli and diarrheagenic E. coli in pork after slaughter, while microbiological testing reduced E. coli. Based on our monitoring data, China urgently needs to establish relevant standards to better control microbial contamination during pig slaughtering progress. This study provided a theoretical basis for the hygiene quality management of the pig slaughter industry in China.